Ticket Sales Accounting Information System Design at PT. Taman Rekreasi Sengkaling UMM - Anik Kusmintarti; Nurafni Eltivia; Aziza Shella Ade Yolandra (The Institute of Academic Research and Publication (IARP), 2023)
The diverse tourism sector with its uniqueness and supported by the facilities and means of transportation available in tourist areas can make it easy for tourists to visit tourist attractions. The development of information and communication technology marked by the existence of the internet has brought society into a new era. The information and communication technology revolution has been marked in which information has become a commodity and a force for those who control it. Based on observations and interviews that the authors conducted in the field and on the internet, there is no website-based application that can map tourist attractions at PT. Taman Rekreasi Sengkaling UMM. This study aims to design and build a website-based tourism ticket sales accounting information system to make it easier for local and foreign tourists to access information and visit tourism objects at PT. Taman Rekreasi Sengkaling UMM. The system design model uses ADDIE. Based on the results of the application design that has been done, namely a website-based ticket booking application. The application can be accessed using the website from a smartphone computer or laptop and can provide information related to existing tourist objects and assist relevant agencies in promoting tourism at the PT. Taman Rekreasi Sengkaling UMM.